2014
DOI: 10.1007/s12594-014-0060-z
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon Source Potential and Depositional Environment of the Surma Group Shales of Bengal Basin, Bangladesh

Abstract: Surma Group is the most important geological unit of Bengal basin, Bangladesh, because petroleum resources occur within this group. It is mainly composed of alternation of shale and sandstone and the shale fraction has long been considered as source rocks and the sandstone fraction as reservoir. These source and reservoir rocks have been studied by different authors by different approach but none of them adopted organic geochemistry and organic petrology as a means of study of source rock and their possible de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Therefore, we divided the columnar samples of the sediments into superficial sediments (0-15 cm) and deeper sediments (15-40 cm) and analyzed the correlation between various N fractions in sediments at different depths and the correlation indicates that organic matter in the deeper sediments of the two study areas mainly originate from endogenous aquatic organisms rather than terrestrial plants. The C/N in sediments within the range of 0-40 cm in Areas B, D and E was higher than that in Areas A and C. This implies that terrestrial plants make a relatively large contribution to organic matter in sediments in Areas B, D and E [23,29]. Differences between the C/N ratios of sediments in different study areas indicate that different areas have different sources of organic matter.…”
Section: The Relationship Between Different N Fractions and Sediment mentioning
confidence: 84%
See 1 more Smart Citation
“…Therefore, we divided the columnar samples of the sediments into superficial sediments (0-15 cm) and deeper sediments (15-40 cm) and analyzed the correlation between various N fractions in sediments at different depths and the correlation indicates that organic matter in the deeper sediments of the two study areas mainly originate from endogenous aquatic organisms rather than terrestrial plants. The C/N in sediments within the range of 0-40 cm in Areas B, D and E was higher than that in Areas A and C. This implies that terrestrial plants make a relatively large contribution to organic matter in sediments in Areas B, D and E [23,29]. Differences between the C/N ratios of sediments in different study areas indicate that different areas have different sources of organic matter.…”
Section: The Relationship Between Different N Fractions and Sediment mentioning
confidence: 84%
“…In addition, TOC levels can also reflect the type and intensity of human activities [28]. The C/N ratio of sediments can be used to infer the source of organic matter and the productivity of a lake to reveal the influences of human activities on the evolution of lake eutrophication [29]. The C/N (by mass) in sediments of different depths in the five study areas indicated that C/N in the deeper sediments (20-40 cm) of Areas A and C were relatively stable and were characterized by a relatively small variation range (Figure 2).…”
Section: Sample Sitementioning
confidence: 99%
“…It is believed that the Bhuban Formation is acting both as source rock (shale part) and reservoir rock (sandstone part) for the existing petroleum system of the Bengal Basin (Imam 2005). So far, there is no detail work published on organic geochemical and petrographical aspects of the Bhuban shales except Farhaduzzaman et al (2014). Here, we present the data from both techniques: Organic geochemical and petrographical for Bhuban Formation shales.…”
Section: Introductionmentioning
confidence: 94%
“…Additionally, it may also have the capacity to generate oil-type hydrocarbons to a lesser quantity due to its organic matter type II/III kerogen. To assess the maturity and kerogen type, the obtained data were plotted on an HI versus Tmax diagram (e.g., [41,47,48]) (Figure 12). This concluded that the Cerrejón Formation in the central area of the Ranchería Sub-Basin has not reached the oil generation window, but it would have the capacity to generate mainly gas-type hydrocarbons due to its organic matter type III kerogen.…”
Section: Quality Of Organic Mattermentioning
confidence: 99%